SEMIOTIKA SOSIAL SEBAGAI ALAT ANALISIS TEKS DALAM PENELITIAN KOMUNIKASI KUALITATIF - Imran, Hasyim Ali (Jurnal Insani, 2014)
This paper discusses the qualitative approach communication with research that is focused on the text as a subject of research. The writing is directed at a sample form of the application practice method in text analysis, that refers to a social semiotics method of MAK Halliday version. In academic, this writing is expected to contribute to ease students in doing practice.